The Effect Of Remedial Learning Using Augmented Reality Media On Student Learning Interest In Cell Material: Pengaruh Pembelajaran Remedial menggunakan Media Augmented Reality terhadap Minat Belajar Siswa pada Materi Sel - Ummah, Allydya Chotibatul; Narsan, Vifty Octanarlia; Utami, Rhodiya Kamalia (SEJ (Science Education Journal), 2024)
Cell material that has the character of Higher Order Thinking Skills (HOTS) and the lack of use of teaching media is one of the causes of students' difficulties in understanding it. In addition, it also has an impact on remedial learning. The purpose of this study is to determine the effect of remedial learning with augmented reality teaching media on students' learning interest in cell material. The research method uses a quantitative approach of the pre-experimental type with a form of research in the form of one group pre-test post-test. The technique used in data retrieval is the purposive sampling technique. The study sample was grade XI2 students of SMA Negeri 1 Seputih Mataram who experienced remedial cell material with a total of 18 individuals (10 men and 8 women) from 34 individuals who experienced remedial in general. The instrument used in the study was a questionnaire with the Guttman type. The aspects studied are 5 indicators of student learning interest: pleasure, focus, a sense of interest in the lesson, great curiosity, and involvement in the teaching and learning process. While the aspects assessed in this study amounted to 20. Based on research, the use of augmented reality media in remedial learning has increased. This can be seen from the average percentage value before treatment of 55.23% which is included in the low category and has increased by 64.94% which is included in the medium category. This proves that remedial learning using augmented reality-based teaching media can increase student interest in learning.